Oxidative Stress, Antioxidant Capacity, and Inflammatory Markers in Patients with Idiopathic Complete Heart Block - Shobhit Shah; Monika Bhandari; Pravesh Vishwakarma; Wahid Ali; Mohammad Kaleem Ahmad; Abhishek Singh; Ayush Shukla; Akhil Kumar Sharma; Gaurav Chaudhary; Akshyaya Pradhan; Sharad Chandra; Rishi Sethi; et al. (Heart Views)
Background: The majority of cases of complete heart block (CHB) still have an idiopathic etiology, despite recent advancements in CHB management. This previously unexplored aspect of CHB is examined in our work. In this study, we sought to evaluate the etiological characteristics of patients with CHB. Materials and Methods: Sixty patients with CHB, ranging in age from 30 to 80 years, who were admitted as inpatients to the emergency room made up the study population. Catalase (CAT) activity, serum malondialdehyde (MDA), serum glutathione (GSH), and serum superoxide dismutase (SOD) activity were used to measure oxidative stress. Serum total antioxidant capacity levels (TAOC) were used to calculate antioxidant activity. Tumor necrosis factor-alpha (TNF-alpha) and serum interleukin-5 (IL-5) levels were used to gauge the degree of inflammation. These numbers were contrasted with those of 30 healthy individuals who had never smoked or had diabetes mellitus. Individuals with drug-induced CHB and acute myocardial infarction were not accepted. Results: Out of 60 patients, the gender distribution was 37 men and 23 women, with a mean age of 62.48 ± 7.98 years. Serum MDA (ng/ml) has a mean value of 1451.26 ± 206.32 in patients and 1197.98 ± 234.71 in controls (P ≤ 0.001). Serum GSH (ug/ml) has a mean value of 46.982 ± 18.613 in patients and 54.155 ± 10.762 in controls (P = 0.027). Serum CAT activity (unit/min/mg protein) has a mean value of 10.763 ± 4.038 in cases and 19.878 ± 7.787 in controls (P = 0.003). Serum SOD activity (unit/g) has a mean value of 24.950 ± 5.4565 in patients and 46.214 ± 14.6309 in controls (P = 0.891). The mean serum total antioxidant capacity (U/ml) for the patients was 5.546 ± 0.620, whereas the controls had a mean value of 8.346 ± 2.781 (P = 0.025). Total antioxidant capacity levels(TOAC) (P = 0.025), GSH (P = 0.027), CAT (P = 0.003), and SOD (P = 0.891) were considerably lower in patients during a CHB compared to the healthy control group, indicating that an increase in oxidative free radicals leads to endothelial dysfunction. High significant increases in MDA (P ≤ 0.001) were indicative of increased reactive oxygen species-mediated tissue damage. Serum IL-5 (pg/ml) has a mean value of 67.347 ± 20.445 (P < 0.001) in controls and 481.442 ± 28.8995 in patients. The patients’ mean serum TNF-alpha value (pg/ml) is 196.741 ± 73.771, whereas the controls’ mean value is 144.530 ± 42.599 (P = 0.081). Conclusions: Serum MDA and inflammatory markers were markedly elevated during a CHB. This is particularly the case with IL-5, which was significantly increased in patients with CHB. According to our research, some inflammatory markers, such as IL-5 and oxidative markers like MDA, may actively contribute to the development of heart block.